Decolorization of Rhodamine B and conversion into saturated fatty acids by laccase-producing fungi isolated from lake sediment - Junjira Thipraksa; Panisa Michu; Alisa Kongthong; Pimprapa Chaijak (Journal of Degraded and Mining Lands Management, 2024)
The persistence of the carcinogenic Rhodamine B dye poses significant risks to human health. Utilizing a unique fungal strain for its degradation offers a sustainable solution to mitigate these hazards. Bioremediation techniques have demonstrated substantial promise in addressing recalcitrant pollutants such as dyes. In this particular study, laccase-producing fungi were carefully chosen for their potential to break down the toxic textile dye Rhodamine B. These selected fungi Cerrena unicolor FBR03 exhibited an impressive maximum degradation rate of 95.10%. Additionally, an analysis using GC-MS revealed the emergence of breakdown products, including 2-cyclopenten-1-one, 3-hydroxy-2-methyl, thymine, dodecanoic acid, tetradecanoic acid, n-hexadecanoic acid, and dibutyl phthalate. These results underscore the potential of this fungal strain as a promising organism for the effective degradation of dye compounds, while simultaneously producing valuable saturated fatty acids as by-products.